2022
DOI: 10.3390/nano12172917
|View full text |Cite
|
Sign up to set email alerts
|

Natural Convection within Inversed T-Shaped Enclosure Filled by Nano-Enhanced Phase Change Material: Numerical Investigation

Abstract: Energy saving has always been a topic of great interest. The usage of nano-enhanced phase change material NePCM is one of the energy-saving methods that has gained increasing interest. In the current report, we intend to simulate the natural convection flow of NePCM inside an inverse T-shaped enclosure. The complex nature of the flow results from the following factors: the enclosure contains a hot trapezoidal fin on the bottom wall, the enclosure is saturated with pours media, and it is exposed to a magnetic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In this regard, Ahmed et al [ 7 ] presented a numerical investigation of the impacts of melting on the convective flow of Al 2 O 3 (nanoparticle)-based PCM within cylindrical tubes containing cross-shape heated sections The results of this study revealed that the flow structures, the irreversibility of the system, and the melting process can be controlled by increasing/decreasing number of the heated fins. Another numerical study on the natural convection within inversed T-shaped enclosure filled by nano-enhanced phase change material (NePCM) was performed by Abderrahmane et al [ 8 ]. Their considered enclosure contains various factors such as a hot trapezoidal fin on the bottom wall, which was saturated with pours media and exposed to a magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Ahmed et al [ 7 ] presented a numerical investigation of the impacts of melting on the convective flow of Al 2 O 3 (nanoparticle)-based PCM within cylindrical tubes containing cross-shape heated sections The results of this study revealed that the flow structures, the irreversibility of the system, and the melting process can be controlled by increasing/decreasing number of the heated fins. Another numerical study on the natural convection within inversed T-shaped enclosure filled by nano-enhanced phase change material (NePCM) was performed by Abderrahmane et al [ 8 ]. Their considered enclosure contains various factors such as a hot trapezoidal fin on the bottom wall, which was saturated with pours media and exposed to a magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, many new works use this kind of fluid in order to expand knowledge about it (Selimefendigil and Öztop, 2018;Chen et al, 2015;Aissa et al, 2023;Laidoudi et al, 2022b;Jamaludin et al, 2021). Also, there is a type of fluid called NEPCM (Aissa et al, 2022a;Sadr et al, 2022;Aissa et al, 2022b;Ghalambaz et al, 2019;Aly et al, 2022), which is one of the manufactured fluids. This kind of suspension is composed of water and very fine capsules.…”
Section: Introductionmentioning
confidence: 99%
“…When used in thermal systems, PCMs provide several benefits. Numerous studies have proven that this strategy has significant promise for successful renewable energy resource usage, waste heat recovery, and thermal management [ 1 , 2 , 3 , 4 ]. Additionally, the capital costs for electrochemical storage devices and LHTES were estimated to be USD 200–300 and USD 70–200 per kWh, respectively [ 5 ].…”
Section: Introductionmentioning
confidence: 99%